ANALISIS TERHADAP PELANGGARAN KODE ETIK NOTARIS DALAM PEMBUATAN AKTA JUAL BELI - Dalilah Agustiani H. Sugandi; Aju Putrijanti (Universitas Muhammadiyah Ponorogo, 2023)
This study examines the analysis carried out on the study of a notary who violates the code of ethics against the sale and purchases deed he made. The research method used is a normative juridical study, namely a study based on legal sources such as legislation, and expert opinions to studies related to the title chosen by the researcher. The result of this research is that he is known as a public official, a notary who makes an authentic deed, one of which is a deed of sale and purchase. In Indonesia itself, several violations of the code of ethics have been committed by notaries based on literature studies conducted by researchers including denial of the contents of the deed of sale and purchase, the notary who did not read the contents of the deed to all parties and the use of false identities. These violations will have an impact on the authenticity of the deed of sale and purchase made by a notary so several consequences must be accepted and faced. what is meant in this case can be in the form of actions taken, notary accountability for actions, and the injured party to sanctions that must be accepted, both administrative, civil and criminal sanctions on the type of error committed. Seeing this phenomenon, a Notary must uphold the Notary's code of ethics in carrying out his profession so as not to abuse his authority based on the principle of prudence at work.